PELATIHAN DESAIN GRAFIS MENGGUNAKAN APLIKASI CANVA PADA PERANGKAT DESA BERINGIN - Cahyaningsih Putri Andaryani; Sarmini; Jefri Prayitno Bangkit Saputra (Nusantara Hasana Journal, 2023)
The rapid development of technology has had a huge impact on village officials who have limited knowledge of technology, especially in the fields of editing and design. The use of editing and design by village officials is used to create attractive promotional materials, such as posters, brochures, banners or pamphlets to promote programs or activities held by village officials. An attractive design can help increase public interest and awareness of these activities. As a solution to support the activities carried out by Beringin village officials, one way that can be done is to hold graphic design training activities by utilizing the Canva application as the application chosen for training media design. The results of this graphic design training are expected to increase the motivation of Banyan village officials in conveying information using the visual arts of graphic design in the era of technological development so that they can adapt to the times.